Ukraine - BEEPS-at-a-glance - World Bank (Washington, DC, 2012)
The EBRD-World Bank Business Environment and Enterprise Performance Survey (BEEPS) is a joint initiative of the European Bank for Reconstruction and Development and the World Bank. The BEEPS has been carried out in three rounds in 1999, 2002, and 2005 and covers virtually all of the countries of Central and Eastern Europe and the former Soviet Union, as well as Turkey. The 2005 round of the BEEPS consisted of two parts: The main BEEPS sample was drawn from the universe of firms in a broad range of economic activities, with the split between services and industry roughly proportional to the contribution to GDP in each country. The main BEEPS sampling approach was the same in all three rounds of the BEEPS. The Manufacturing Overlay refers to additional manufacturing firms that were added, above and beyond the Main BEEPS sample, in selected countries. The BEEPS covers a broad range of issues about the business environment, and this note on Ukraine presents some simple indicators for key areas: problems doing business; unofficial payments and corruption; crime; regulations and red tape; customs and taxes; labor issues; firm financing; legal and judicial issues; and infrastructure.